(untitled) (Research, Society and Development, 2021)
The study aimed to understand the child with Autistic Spectrum Disorder (ASD) in early childhood (from zero to two years), reflecting on the constructive possibilities of Art Education for the child’s development and learning. TEA is characterized by difficulties in language development, communication processes and deficits in socialization processes. Art can provide sensory, cognitive and affective experiences and construction opportunities, and which dialogues with therapeutic-pedagogical interventions in the education of atypical children with difficulties in social interaction and communication. The qualitative research was carried out through a narrative interview with the mother of a child with ASD. The results suggest that the child showed signs of ASD from the first months: difficulty in breastfeeding, the absence of eye contact, discontent in the moments of touch, little reaction to the human voice, fixation by objects that could be rotated and a repetitive pattern of organization. Art awakens multiple sensations in the baby: it creates affective bonds, promotes coziness, stimulates sensory perceptions and movement and needs to be stimulated for this expression. It is concluded that the child with ASD in early childhood, can benefit from the constructive possibilities of Art-Education, as a beneficial factor for the child’s interactive progress.